Stressors and counseling needs of undergraduate nursing students in Ibadan, Nigeria (2004)
Existing evidence suggests that nursing students have high levels of stress and that counseling and other support services should be made available to them. However, the stressors and counseling needs of undergraduate nursing students in Nigeria have yet to be explored. This study used a questionnaire to investigate the: stressors, counseling deeds, and desired counseling facilities of undergraduate nursing students at the University of Ibadan. Common stressors included excessive school work; financial 'problems, inadequate recreational facilities, and overcrowded accommodations. There was an association between reporting inconsiderate, insensitive lecturers as stressors and evidence of psychological distress. Nearly 60% of the respondents felt counseling would help them, and most desired counseling for academics, finances, and relationships. Most (78%) of the respondents preferred an independent facility with trained counselors. Desired characteristics for the services included accessibility, affordability, confidentiality, and a friendly atmosphere. Educators and administrators should use this information to design counseling facilities for students